Inhibition of glioma growth by flavokawain B is mediated through endoplasmic reticulum stress induced autophagy. Issue 11 (2nd November 2018) - Wang, Jiwei; Qi, Qichao; Zhou, Wenjing; Feng, Zichao; Huang, Bin; Chen, Anjing; Zhang, Di; Li, Wenjie; Zhang, Qing; Jiang, Zheng; Bjerkvig, Rolf; Prestegarden, Lars; et al.
ABSTRACT: Flavokawain B (FKB), a natural kava chalcone, displays potent antitumor activity in various types of cancer. The mechanism of action, however, remains unclear. Here, we evaluated the efficacy of FKB in the treatment of human glioblastoma multiforme (GBM) as well as the molecular basis for its inhibitory effects in cancer. Approximately 60% of GBM cells became senescent after treatment with FKB as assessed in the senescence-associated (SA)-GLB1/SA-β-galactosidase assay. The cellular process of autophagy potentially contributed to the establishment of senescence. Transmission electron microscopy revealed the formation of autophagic vesicles under FKB treatment, and MAP1LC3B (microtubule associated protein 1 light chain 3 beta)-II was increased. Transfection of ATG5 or ATG7 small interfering RNAs (siRNAs) inhibited FKB-induced autophagy in U251 cells. Western blot revealed that molecular components of the endoplasmic reticulum stress pathway were activated, including ATF4 (activating transcription factor 4) and DDIT3 (DNA damage inducible transcript 3), while levels of TRIB3 (tribbles pseudokinase 3) increased. In addition, based on the phosphorylation status, the AKT-MTOR-RPS6KB1 pathway was inhibited, which induced autophagy in GBM cells. Inhibition of autophagy by autophagy inhibitors 3-methyladenine and chloroquine or knockdown of ATG5 or ATG7 caused FKB-treated U251 cells to switch from senescence to apoptosis. Finally, knockdown of ATG5 or treatment with chloroquine in combination with FKB, significantly inhibited tumor growth in vivo . Our results demonstrated that FKB induced protective autophagy through the ATF4-DDIT3-TRIB3-AKT-MTOR-RPS6KB1 signaling pathway in GBM cells, indicating that the combination treatment of FKB with autophagy inhibitors may potentially be an effective therapeutic strategy for GBM. Abbreviations: 3-MA: 3-methyladenine; 4-PBA: 4-phenylbutyrate; AKT: AKT serine/threonine kinase; ATF4: activating transcription factor 4; ATG: autophagy related; CASP3: caspase 3; CCK-8: cell counting kit-8; CDKN1A: cyclin-dependent kinase inhibitor 1A; CQ: chloroquine; DDIT3: DNA damage inducible transcript 3; DMEM: Dulbecco's modified Eagle's medium; EIF2A: eukaryotic translation initiation factor 2A; EIF2AK3: eukaryotic translation initiation factor 2 alpha kinase 3; ER: endoplasmic reticulum; FKB: flavokawain B; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GBM: glioblastoma multiforme; GFP: green fluorescent protein; HSPA5: heat shock protein family A (Hsp70) member 5; MAP1LC3B: microtubule associated protein 1 light chain 3 beta; MTOR: mechanistic target of rapamycin kinase; PARP1: poly(ADP-ribose) polymerase; 1RPS6KB1: ribosomal protein S6 kinase B1; SA-GLB1: senescence-associated galactosidase beta 1; siRNA: short interfering RNA; SQSTM1: sequestosome 1; TEM: transmission electron microscopy; TRIB3: tribbles pseudokinase 3; TUNEL: deoxynucleotidyl transferase-mediated dUTP nick-end labeling